Isolation and Characterization of a Silicate-Solubilizing Bacterial Strain Associated with the Roots of Groundnut (Arachis hypogaea L.) - Ruban P; P.R.Jeyaramraja (Indonesian Journal of Agriculture and Environmental Analytics, 2023)
The aim of this investigation was to isolate groundnut root-associated rhizobacteria and to study their efficiency to solubilize silicate, synthesize indole acetic acid (IAA), encourage plant growth, and promote silicon (Si) uptake and deposit in plants. Based on silica-solubilizing ability and IAA production, a bacterial strain was chosen in the present study for further studies. The bacterial isolate synthesized more quantities of IAA at pH 8. When the soil fertilized with silica was inoculated with this bacterial strain, there was an improvement in overall growth characteristics of groundnut. It was also found that more Si was deposited in plants fertilized with both insoluble silica and bacterial strain. Bacteria isolated in the present study can synthesize more IAA under alkaline conditions, solubilize silicate, and encourage the growth of groundnut.